2019
DOI: 10.1111/aji.13210
|View full text |Cite
|
Sign up to set email alerts
|

Depot medroxyprogesterone acetate and norethisterone enanthate differentially impact T‐cell responses and expression of immunosuppressive markers

Abstract: Problem: Injectable contraceptive use may impact immune cell responsiveness and susceptibility to infection. We measured responsiveness of T-cells from women before and after initiating depot medroxyprogesterone acetate (DMPA) or norethisterone enanthate (Net-En). Method of study: Peripheral blood mononuclear cells collected from women aged18-34 years prior to, at steady state, and nadir concentrations after initiating DMPA (n = 30) or Net-En (n = 36) and from women initiating copper intrauterine device (CU-IU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
1
3
1
Order By: Relevance
“…Findings from our two studies suggest T cell-related immune system changes that occur in DMPA users and that could impact susceptibility to infections including HIV, consistent with in vitro studies demonstrating reduction in T-cell release of IFNγ and TNFα following MPA exposure. [19][20][21]26 However, we also demonstrated that physiologic exposure to DMPA did not significantly reduce the proportion of IL-4-and IL-13-producing T cells after six months of use, a finding that differs from published studies of T cells exposed to MPA in vitro. 21,22,31 Following intramuscular injection with 150 mg DMPA, serum MPA concentrations rise to ~25 ng/ml within days and decline to between 1-9 ng/ml over the subsequent 12-week dosing period.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…Findings from our two studies suggest T cell-related immune system changes that occur in DMPA users and that could impact susceptibility to infections including HIV, consistent with in vitro studies demonstrating reduction in T-cell release of IFNγ and TNFα following MPA exposure. [19][20][21]26 However, we also demonstrated that physiologic exposure to DMPA did not significantly reduce the proportion of IL-4-and IL-13-producing T cells after six months of use, a finding that differs from published studies of T cells exposed to MPA in vitro. 21,22,31 Following intramuscular injection with 150 mg DMPA, serum MPA concentrations rise to ~25 ng/ml within days and decline to between 1-9 ng/ml over the subsequent 12-week dosing period.…”
Section: Discussioncontrasting
confidence: 89%
“…We also reported that T-cell response to ex vivo stimulation is suppressed at steadystate MPA concentrations and resolves at nadir concentration suggesting transient immunosuppression. 26 The results presented here further our prior work and demonstrate that after 180 days of injectable contraceptive use, at nadir hormone concentrations, physiologically exposed T cells have depleted cytokine production. Findings from our two studies suggest T cell-related immune system changes that occur in DMPA users and that could impact susceptibility to infections including HIV, consistent with in vitro studies demonstrating reduction in T-cell release of IFNγ and TNFα following MPA exposure.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…For example, the etonorgestrel implant has been associated with impaired sexual function, thought to be related to suppression of estrogen and testosterone [ 20 ], but we do not have robust data comparing this effect with other methods. Intramuscular norethisterone enanthate has many similar behavioural effects to DMPA-IM, but less glucocorticoid and immunosuppressive effects] [ 21 , 22 ]. This might confer a similar reduction in exposure without increased immune susceptibility and thus lower net risk of HIV.…”
Section: Discussionmentioning
confidence: 99%
“…The methods of hormonal contraception such as intramuscular DMPA injections, copper intrauterine spirals, and levonorgestrel implants were considered safe. However, despite the updated WHO guidelines, the use of DMPA remains controversial and raises questions among specialists, since extensive clinical and laboratory data indicate that this contraceptive can still increase the risk of HIV infection [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. A number of epidemiological studies indicate that women living with HIV-1 who use hormonal contraception, compared with HIV-positive women who do not, have a significantly higher viral load, simultaneous infection with several HIV-1 genotypes, and more accelerated CD4+T cell loss, which correlates with increased mortality among this cohort [ 14 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%